Evaluating folic acid supplementation among Japanese pregnant women with dietary intake of folic acid lower than 480 µg per day: results from TMM BirThree Cohort Study. (4th March 2022) - Kikuchi, Daisuke; Obara, Taku; Usuzaki, Takuma; Yonezawa, Yudai; Yamashita, Takahiro; Oyanagi, Gen; Noda, Aoi; Ueno, Fumihiko; Murakami, Keiko; Matsubara, Hiroko; Ishikuro, Mami; Metoki, Hirohito; et al.
Abstract: Objective: In Japan, supplementation with 400 µg of folic acid per day is recommended for women who are planning to get pregnant to decrease the risk of their babies getting neural tube defects (NTD). However, the proportion of women who have taken folic acid supplements before conception is low among Japanese pregnant women. In addition, the dietary intake of folic acid has not yet reached the government recommended dietary intake levels (480 µg per day). This study aimed to clarify the prevalence and determinants of adequate folic acid supplements among Japanese pregnant women with dietary folic acid intake lower than 480 µg per day. Methods: This cross-sectional study was a part of the Tohoku Medical Megabank Project Birth and Three-Generation Cohort Study. We collected information on folic acid supplements before conception, sociological/lifestyle characteristics, and food consumption. The primary outcome was the use of folic acid supplements (adequate or inadequate, based on the timing of initiation of folic acid supplements). Multiple logistic regression analysis was used to examine the association between sociological/lifestyle characteristics and the adequate intake of folic acid supplements. Results: Among the 11, 562 pregnant women who took lower than 480 µg per day of folic acid from food, the prevalence of adequate users was 18.0%. Pregnant women who reported adequate use of folic acid supplements were more likely to be older and educated; and reported higher household income, and history of fertility treatment. Conversely, they were less likely to be ever or current smokers and multipara. Conclusion: This study found that the prevalence of folic acid supplements use for the prevention of NTD among Japanese pregnant women was still low.